Improving the performance of applicators for use in hyperthermia cancer treatment procedure by the introduction of LHM lens / Nabilah Abdul Jaffar ...[et al.] - Abdul Jaffar, Nabilah; Lias, Kasumawati; Madzhi, Nina Korlina; Buniyamin, Norlida (Universiti Teknologi MARA, 2019)
This paper describes the improvement of applicator performance used for Non-invasive Hyperthermia Cancer Treatment Procedure (NIHCT). Current available applicators have poor focal spot when directed towards an actual tumor area. A literature review indicated that Left-Handed Metamaterial (LHM) lens when integrated with an antenna can improve focusing capabilities of the antenna to treat the cancerous area. Subsequently, a proposed modified applicator that integrates LeftHanded Metamaterial (LHM) lens with existing antenna is discussed. The applicator performance is improved by the integration of Left-Handed Metamaterial (LHM) lens to a microstrip antenna. The proposed antenna termed LHMA is expected to have an improved focusing capability which could be used to kill cancerous tissues without severely affecting surrounding healthy tissues. The goal of the research is to reduce unwanted hot-spots using the proposed applicators. The applicator for NIHCT procedure used LHM lens by adjusting the applicator distance towards the cancerous area and varying the thickness of the LHM lens. SEMCAD X simulator software was used to execute electromagnetic and thermo simulation, analysis and modification of the simulated antenna where two shapes of lens were used. The focusing abilities of the proposed applicator was evaluated using the Specific Absorption Rate (SAR) area obtained. The results shows that Cylindrical LHM lens gives better focusing effect rather than flat rectangular LHM lens.